Analysis of the Socio-economic Contributions of Rincon de la Vieja national park “Conservation with Soul of Volcano” World Natural Heritage Site UNESCO 2009 - Salas Pinel, Fiorella (2001)
The Project Systematization and Analysis of the Contributions of National Parks and Biological Reserves to the Economic and Social Development in Costa Rica, Benin and Bhutan is executed under the Program of South-South Cooperation, financed by the Kingdom of the Netherlands and administrated by Fundecooperacion. This project is led by the International Centre for Sustainable Development of Policy (CINPE) of the Universidad Nacional (UNA) of Costa Rica, which performs the general coordination. The counterpart in Benin is the Centre pour l'Environnement Béninois et le Développement Economique et Social (CEBEDES). While in Bhutan is the Division of Nature Conservation of the Ministry of Agriculture and Forests of the Royal Government of Bhutan. The project's general objective is to systematize and analyze the socio-economic contribution –centralized and decentralized- "of national parks and biological reserves to the economic and social development of Costa Rica, Bhutan and Benin and make policy recommendations of management to support policy makers in the management of national parks and biological reserves. Rincon de la Vieja National Park (PNRV), which is part of the Guanacaste Conservation Area (ACG, Site of World Natural Heritage UNESCO), is one of the three case studies analyzed in Costa Rica. The same one that was selected by a group of experts to meet various criteria, which place it as a Protected Wildlife Area of priority in terms of water resources, diversity of landscapes, ecosystems and species, research, potential for energy generation, generation of environmental services, and national and international relevance, among others. The methodology used in the study combines cluster analysis with a dynamics of added value chain. Where PNRV constitutes the material basis that underpins the existence and reproduction of diverse socio-economic activities that depend directly and indirectly on their preservation. These activities report qualitative and quantitative contributions to various social actors at local, regional, national and international levels. In an effort to translate these contributions in monetary terms, the search, systematization and analysis of primary and secondary information allows an approximate estimation of the contributions of PNRV for 2009. In this regard, the overall contribution of Rincon de la Vieja National Park is approximately 12.8 billion colones (US$ 23,010,302). This implies about 282 million colones (US$ 507,810) at the local level. Meanwhile, the regional level reports an amount close to 2.3 billion colones (US$ 4,169,121), the national level of 2.3 billion colones (US$ 4,258,638), and 7.8 billion colones (US$ 14,074,733 ) at international level.